Poly- and perfluoroalkyl substances (PFAS) exposure through infant feeding in early life. (June 2022) - van Beijsterveldt, Inge A.L.P.; van Zelst, Bertrand D.; de Fluiter, Kirsten S.; van den Berg, Sjoerd A.A.; van der Steen, Manouk; Hokken-Koelega, Anita C.S.
Graphical abstract: Highlights: Human milk contains measurable amounts of PFOA and PFOS. Daily PFAS intake is highest in exclusively breastfed infants of older mothers. Daily PFAS intake is highly correlated with PFAS plasma levels throughout infancy. Breastfeeding is an important exposure pathway of PFOA and PFOS in early life. Knowing the important health benefits of breastfeeding, our findings warrant more research. Abstract: Background and aims: Per- and polyfluoroalkyl substances (PFAS) are non-degradable, man-made-chemicals with an elimination half-life of multiple years, causing accumulation in the environment and humans with potential harmful effects. However, longitudinal PFAS levels in human milk, daily PFAS intake and the association with infant plasma PFAS levels have never been reported. We investigated longitudinal PFOA and PFOS levels in human milk and the daily PFAS intake through infant feeding in the first 3 months of life, the most important determinants and the correlation with PFAS plasma levels at age 3 months and 2 years. Methods: In 372 healthy term-born Dutch infants, we determined PFOA and PFOS levels in human milk given at age 1 and 3 months, in 6 infant formula brands and in infant plasma at 3 months and 2 years, using liquid-chromatography-electrospray-ionization-tandem-mass-spectrometry(LC-ESI-MS/MS). We studied the associations between daily PFAS intake and predictive characteristics by multiple regression models. Results: PFOA and PFOS levels in human milk decreased between 1 and 3 months after delivery, regardless whether breastfeeding was given exclusively(EBF) or in combination with formula feeding. PFOA and PFOS could not be detected in any formula feeding. Daily PFAS intake(ng/kg) was highest in EBF-infants. Higher amount of human milk, older maternal age, lower parity and first-time breastfeeding were associated with higher daily intake. Daily PFAS intake in early life was strongly correlated with PFAS plasma levels at age 3 months and 2 years(R = 0.642–0.875, p < 0.001). Conclusions: Human milk contains PFOA and PFOS, in contrast to formula feeding. Daily PFOA and PFOS intake in early life is highest in exclusively breastfed infants and it is highly correlated with infant's plasma levels throughout infancy. Our findings show that breastfeeding is an important PFAS exposure pathway in the first months of life, with unknown but potential adverse effects. Knowing the important health benefits of breastfeeding, our findings warrant more research about the health outcomes in later life.